2023
DOI: 10.1186/s40462-023-00435-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level patterns of resource selection do not predict hotspots of contact

Anni Yang,
Raoul Boughton,
Ryan S. Miller
et al.

Abstract: Contact among animals is crucial for various ecological processes, including social behaviors, disease transmission, and predator–prey interactions. However, the distribution of contact events across time and space is heterogeneous, influenced by environmental factors and biological purposes. Previous studies have assumed that areas with abundant resources and preferred habitats attract more individuals and, therefore, lead to more contact. To examine the accuracy of this assumption, we used a use-available fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Our analyses emphasize the importance of this next step by showing that correlations at a local (cell) scale can create a vastly more heterogeneous transmission landscape. Moreover, correlations can lead to localized transmission hotspots that are not necessarily predictable from joint space use (Yang et al, 2023a), and may contribute to the growing empirical recognition that fine-scale, localized transmission hotspots are present in many empirical host-pathogen systems (Albery et al, 2021). Whether these localized transmission hotspots are predictable a priori remains to be seen, but ignoring correlated movements can make the task orders of magnitude more difficult for some pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses emphasize the importance of this next step by showing that correlations at a local (cell) scale can create a vastly more heterogeneous transmission landscape. Moreover, correlations can lead to localized transmission hotspots that are not necessarily predictable from joint space use (Yang et al, 2023a), and may contribute to the growing empirical recognition that fine-scale, localized transmission hotspots are present in many empirical host-pathogen systems (Albery et al, 2021). Whether these localized transmission hotspots are predictable a priori remains to be seen, but ignoring correlated movements can make the task orders of magnitude more difficult for some pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This limits our ability to ask questions like: how do non-independent movements affect spatio-temporal infection risk, compared to spatial overlap? Moreover, recent studies have shown that spatial transmission risk can be highly localized (Albery et al, 2021) and is not necessarily predicted by animal space use (Yang et al, 2023a). We hypothesize that non-independent animal movements can (at least partially) account for these observations and develop a modeling approach to rigorously test this hypothesis and systematically quantify the contribution of space use and correlated movements to spatio-temporal transmission risk.…”
Section: Introductionmentioning
confidence: 99%